2005
DOI: 10.1143/jjap.44.1838
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Glass Addition on Microwave Dielectric Properties of Zn0.95Mg0.05TiO3 + 0.25TiO2 Ceramics

Abstract: The effects of Bi2O3 addition on the microwave dielectric properties and the microstructures of Zn0.95Mg0.05TiO3 + 0.25TiO2 with 1 wt% 3ZnO–B2O3 (ZnBO–ZMT') ceramics prepared by conventional solid-state routes have been investigated. In a preliminary study, it was shown that ZnBO–ZMT' ceramics can be sintered to a theoretical density higher than 95% at 900°C. In this study, the effects of Bi2O3 additions of up to 10 wt% on the sintering characteristics of the ZnBO–ZMT' ceramics was investigated at the sinterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Unlike the Nb-ZMT ceramics with Bi 2 O 3 addition, the ZMT ceramics with increasing amounts of Bi 2 O 3 show slightly variation of dielectric constant. In a previous study, 11 we have investigated the microwave dielectric properties of the ZMT ceramics with different amounts of Bi 2 O 3 addition. A comparison between the ceramics with and without Nb 2 O 5 dopant on the microstructure of the ceramics will be described briefly below.…”
Section: Effect Of Bi 2 O 3 Addition On Microwave Dielectric Propertimentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the Nb-ZMT ceramics with Bi 2 O 3 addition, the ZMT ceramics with increasing amounts of Bi 2 O 3 show slightly variation of dielectric constant. In a previous study, 11 we have investigated the microwave dielectric properties of the ZMT ceramics with different amounts of Bi 2 O 3 addition. A comparison between the ceramics with and without Nb 2 O 5 dopant on the microstructure of the ceramics will be described briefly below.…”
Section: Effect Of Bi 2 O 3 Addition On Microwave Dielectric Propertimentioning
confidence: 99%
“…In the previous study, 11 the microstructure and dielectric properties of the Bi 2 O 3 additive in Zn 0.95 Mg 0.05 TiO 3 + 0.25TiO 2 with 1 wt.% 3ZnO-B 2 O 3 ceramics have been investigated. It was found that 5 wt.% Bi 2 O 3 addition can significantly suppress spinel Zn 2 TiO 4 phase formation in the ZMT ceramics, but the microwave dielectric properties become worse due to low Q value (<600).…”
Section: Introductionmentioning
confidence: 99%
“…Only noble metals like palladium and platinum can be employed. Therefore, the use of such ceramics will increase manufacturing cost in terms of money and energy [6,7]. 0.95MgTiO 3 -0.05CaTiO 3 ceramics were mixed with low-softening-temperature glass materials to reduce the sintering temperature [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…These materials are expensive, their electrical performance is poor, and the cost-effective fabrication of high-quality components is difficult. Several methods are commonly used for lowering the sintering temperature of dielectric ceramics, such as: the addition of glass; chemical pre-treatment and processing of ceramic powders; and the addition of small particles of starting materials [10][11][12]. Of these three methods, liquid-phase sintering with glass addition is generally known to be the most effective and the least expensive way of achieving high density sintered ceramics [13,14].…”
Section: Introductionmentioning
confidence: 99%